2023
DOI: 10.1063/5.0155302
|View full text |Cite
|
Sign up to set email alerts
|

The role of dephasing for dark state coupling in a molecular Tavis–Cummings model

Abstract: The collective coupling of an ensemble of molecules to a light field is commonly described by the Tavis–Cummings model. This model includes numerous eigenstates that are optically decoupled from the optically bright polariton states. Accessing these dark states requires breaking the symmetry in the corresponding Hamiltonian. In this paper, we investigate the influence of non-unitary processes on the dark state dynamics in the molecular Tavis–Cummings model. The system is modeled with a Lindblad equation that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Despite the large number of theoretical studies in the literature, the understanding of the underlying microscopic and macroscopic physical mechanisms, especially with respect to the effects of VSC, is still incomplete and under discussion. , To better understand the formation of molecular vibrational polaritons and their role in polaritonic chemistry, a reliable theoretical description is needed that can also accurately treat the in practice most relevant case of collective strong coupling. One way to achieve such a description is to perform time-dependent simulations in the VSC regime that capture the dynamics of the system and yield optical spectra and changes in chemical reactivity. These explicit time domain calculations have their advantages in simulating complex and anharmonic dynamics but suffer from high computational cost, especially when the dynamics are calculated in an ab initio framework.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of theoretical studies in the literature, the understanding of the underlying microscopic and macroscopic physical mechanisms, especially with respect to the effects of VSC, is still incomplete and under discussion. , To better understand the formation of molecular vibrational polaritons and their role in polaritonic chemistry, a reliable theoretical description is needed that can also accurately treat the in practice most relevant case of collective strong coupling. One way to achieve such a description is to perform time-dependent simulations in the VSC regime that capture the dynamics of the system and yield optical spectra and changes in chemical reactivity. These explicit time domain calculations have their advantages in simulating complex and anharmonic dynamics but suffer from high computational cost, especially when the dynamics are calculated in an ab initio framework.…”
Section: Introductionmentioning
confidence: 99%
“…118−120 In addition to the photon decay, pure dephasing has also been found to influence the polaritonic effects. 121 A more detailed study with the inclusion of these energy losses within the cavity and dephasing would be required to ascertain their effects on the dynamics of the chemiluminescent processes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The role of cavity photon decay and dephasing was not considered in this work. In a recent theoretical study by Rubio and co-workers on cavity influences on thermal Diels–Alder reactions, the impact of cavity losses have been found to be small, although several other studies have reported the significant influences of photon loss on photochemical reactions. In addition to the photon decay, pure dephasing has also been found to influence the polaritonic effects . A more detailed study with the inclusion of these energy losses within the cavity and dephasing would be required to ascertain their effects on the dynamics of the chemiluminescent processes.…”
Section: Resultsmentioning
confidence: 99%
“…In chemistry, the electronic strong coupling, the quantum yield of emissions or intersystem crossings can be modified and photochemical reactions can be influenced. For vibrational strong coupling even ground-state (thermally driven) chemical reactions can be affected However, despite a plethora of suggested applications and observed novel effects, we still lack a fundamental understanding of all the relevant underlying microscopic/macroscopic physical mechanisms, specifically in the context of vibrational strong coupling effects. ,, One of the main reasons for this deficiency is the complexity of the full description, which a priori requires a holistic approach combining the expertise from different fields of physics and chemistry such as quantum optics, electronic structure theory, (quantum) statistical mechanics, quantum electrodynamics, and molecular and solid state physics . Besides questions concerning the observed resonance conditions, currently one of the most pressing, unresolved issues in the field is how individual molecules can experience cavity-induced modifications under collective strong coupling. ,,, Theoretical attempts to determine how the coupling of the cavity to the ensemble of molecules can modify the chemistry of individual molecules in the thermodynamic limit have so far only been able to describe certain aspects. While there have been theoretical suggestions that collective strong coupling can lead to local changes once impurities or (thermally induced) disorder is introduced in an ensemble, , the existence and nature of such effects for a large ensemble of molecules has remained elusive. In this letter we close this important gap by demonstrating numerically that the cavity can indeed induce local polarization effects akin to those observed for small molecular ensembles for collective coupling in the thermodynamic limit, when treating the many-molecule problem self-consistently within the cavity Born–Oppenheimer approximation of the full Pauli–Fierz theory.…”
mentioning
confidence: 99%
“… 6 , 11 , 27 , 28 Theoretical attempts to determine how the coupling of the cavity to the ensemble of molecules can modify the chemistry of individual molecules in the thermodynamic limit have so far only been able to describe certain aspects. 33 36 While there have been theoretical suggestions that collective strong coupling can lead to local changes once impurities or (thermally induced) disorder is introduced in an ensemble, 37 , 38 the existence and nature of such effects for a large ensemble of molecules has remained elusive. In this letter we close this important gap by demonstrating numerically that the cavity can indeed induce local polarization effects akin to those observed for small molecular ensembles 38 for collective coupling in the thermodynamic limit, when treating the many-molecule problem self-consistently within the cavity Born–Oppenheimer approximation of the full Pauli–Fierz theory.…”
mentioning
confidence: 99%